2020
DOI: 10.1161/hypertensionaha.120.15528
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Cardiac Biomarkers in Predicting Mortality of Inpatients With COVID-19

Abstract: The prognostic power of circulating cardiac biomarkers, their utility, and pattern of release in coronavirus disease 2019 (COVID-19) patients have not been clearly defined. In this multicentered retrospective study, we enrolled 3219 patients with diagnosed COVID-19 admitted to 9 hospitals from December 31, 2019 to March 4, 2020, to estimate the associations and prognostic power of circulating cardiac injury markers with the poor outcomes of COVID-19. In the mixed-effects Cox model, after adjusting for age, sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
121
2
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(145 citation statements)
references
References 19 publications
6
121
2
6
Order By: Relevance
“…Interestingly, our study confirms the major role of obesity, low oxygen saturation and high troponin levels in predicting mortality and need for a mechanical ventilation, as recently outlined [ 26 , 27 ]. These variables can be used as useful prognostic markers together with other cardiac and coagulation parameters [ 5 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, our study confirms the major role of obesity, low oxygen saturation and high troponin levels in predicting mortality and need for a mechanical ventilation, as recently outlined [ 26 , 27 ]. These variables can be used as useful prognostic markers together with other cardiac and coagulation parameters [ 5 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…In 28 studies [ 13 15 , 25 – 27 , 31 , 32 , 34 , 37 , 38 , 41 , 43 – 46 , 48 , 49 , 51 , 52 , 55 , 57 , 61 , 65 , 67 , 68 , 70 , 71 ], data on the relationship between troponins (on admission or during hospital stay) and mortality of patients with covid-19 could be extracted. The risks of bias of these studies in assessing the prognostic value of troponins are summarised in Table S 4 .…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a meta-analysis of 11 studies (13,889 patients) that reported multivariable-adjusted associations between admission troponins above the upper reference limit and mortality [ 13 15 , 26 , 27 , 32 , 37 , 45 , 46 , 55 , 67 ]. Elevated troponins on admission were associated with an increased risk of death (RR 2.68, 95% CI 2.08–3.46).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,19,20 Interestingly, elevated troponin levels, a marker of cardiac injury, predicted increased need for mechanical ventilation in multivariable analysis whereas chronic statin use was associated with reduced in-hospital mortality, further underscoring the strong link between underlying cardiovascular disease and worse outcomes with COVID-19. 8,[21][22][23][24][25][26][27][28][29] Importantly, we developed two novel prediction models to calculate risk of hospitalized COVID-19 developing severe outcomes. These models were effective at predicting risk of ventilation need and death in both our derivation and validation cohorts.…”
Section: Discussionmentioning
confidence: 99%